2021
DOI: 10.1021/acsomega.1c05493
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Connectionist Models for Performance Prediction of Low Salinity Waterflooding in Sandstone Reservoirs

Abstract: Low salinity waterflooding (LSWF) and its variants also known as smart water or ion tuned water injection have emerged as promising enhanced oil recovery (EOR) methods. LSWF is a complex process controlled by several mechanisms and parameters involving oil, brine, and rock composition. The major mechanisms and processes controlling LSWF are still being debated in the literature. Thus, the establishment of an approach that relates these parameters to the final recovery factor (RFf) is vital. The main objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 161 publications
0
8
0
Order By: Relevance
“…For example, Bormann [3] suggested that 10% missing precipitation values of the calendar days are the threshold for removing the whole winter observations from the analysis. In contrast, Tatar et al [4] stated that a threshold of 50% missing features was excluded from the prediction of low salinity waterflooding, while imputation of mean value was applied for missing features below the missing threshold.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bormann [3] suggested that 10% missing precipitation values of the calendar days are the threshold for removing the whole winter observations from the analysis. In contrast, Tatar et al [4] stated that a threshold of 50% missing features was excluded from the prediction of low salinity waterflooding, while imputation of mean value was applied for missing features below the missing threshold.…”
Section: Introductionmentioning
confidence: 99%
“…In this research work, a threshold of 50% was considered according to previous research studies. 44 As shown in Table 1 , no parameter has more than 50% missing values, and therefore, they remain. For the other parameters, the missing values are replaced with the mean value of the parameter which is a widely used method for estimating missing values for numeric features.…”
Section: Methodsmentioning
confidence: 99%
“…A parameter must be eliminated if the parameter has many missing values or the percentage of missing values exceeds a certain threshold. In this research work, a threshold of 50% was considered according to previous research studies . As shown in Table , no parameter has more than 50% missing values, and therefore, they remain.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to imputation, it is necessary to ensure that there is a sufficient amount of data for imputation. If a column has more than 50% of data missing, then it is dropped, and the attempt for imputation is dismissed. , Missingno and Bilogur’s method was used to illustrate the missing values. Missing values from the database are shown in Figure .…”
Section: Data Collection and Pre-processingmentioning
confidence: 99%